PEMBINAAN MASJID DAN MUSHALA OLEH IKATAN DAI INDONESIA (IKADI) KOTA PADANG DI KELURAHAN BUKIT GADO-GADO KECAMATAN PADANG SELATAN KOTA PADANG - Fajri Ahmad (Universitas Islam Negeri Imam Bonjol Padang, 2020)
The historical journey of the Prophet Muhammad migrated from Mecca to Medina as a momentum to develop human civilization, which was first built was a mosque, a mosque used as a place of worship to Allah SWT as a center of community activities such as deliberation and relationship. The step taken to prosper the mosque is to build worshipers ranging from children to the elderly. The location of this research is in Bukit Gado-Gado Sub-District, Padang South District, Padang City conducted by the Indonesian Dai Association (IKADI) of Padang City with research sites in Jabal Din Mosque and At-Taqwa Mushala, Al-Amiin and Al-Ikhlas. While the methodology used is field research that is field research using interview data, observation and documentation method then explained clearly and concluded. Guidance is carried out in the mosque and each mushala is in terms of spiritual and intellectual aspects, coaching in the spiritual aspect of reviving the recitation in the mosque such as lecture and sermon review periodically and continuously as well as praying five times a time to worship in the mosque and mushala, on the intellectual aspects in the mushala by participating in teaching the alquran education park and guiding and evaluating studen routinely in accordance with the teaching curriculum of the al-quran education park, at the adolescent level carrying out wirid remaja by providing material relevant to the development of adolescents, in the field of majlis taklim in the mosque encouraging association to hold majlis taklim which synergizes with mosque and mosque leaders and community leaders